Computer Aided Design and Finding the Optimum Dimensions for a Section of a Rotary Jib Crane Arm - كفا, سمير; نجار, رائد; غدير, مجدلين (Latakia University Journal -Engineering Sciences Series, 2021)
Today, the systems of transportation and shipping of goods play a significant role in the work of any industrial establishment. These systems are intended to help workers move objects from one point to another starting with light weights up to 1,000 tons. Rotary Jib cranes are considered to be one of the most commonly used cranes for its comprehensive utilization in terms of the load that they can lift and the requirements that they meet. Thus they are widely used in factories for handling operations and in industrial and mechanical workshops that require transporting small loads. This research discussed the possibility of finding a solution to the design problems that arise during the crane failure, where failure is defined as the sudden loss of structural safety by failure of the material. The considered crane was modeled by Inventor, and then the finite element method (FEM) was used to find the optimal design of the crane through modified the crane arm by studying several sections to obtain the best section, thus avoiding the risks resulting from the possible failure in the most dangerous section, and reducing crane cost.